PENGARUH LINGKUNGAN KERJA DAN KOMPENSASI TERHADAP KINERJA KARYAWAN PADA PT. INDOMARCO PRISMATAMA AREA CIPUTAT - Anjas Firmansyah; Budhi Prabowo (Journal of Research and Publication Innovation, 2025)
The purpose of this study was to determine the effect of the work environment and compensation on employee performance partially or simultaneously at PT. Indomarco Prismatama Area Ciputat. This type of research is descriptive quantitative using a saturated sample, namely the entire population is used as a sample, namely as many as 60 respondents. Based on the results of the first hypothesis test, it was obtained that the value of t count > t table or 1.932 > 2.00030 was reinforced by the Sig value. <0.05 or 0.000 <0.05 H0 is rejected and H1 is accepted. So it can be concluded that partially the Work Environment Variabel has a significant influence on Employee Performance at PT Indomarco Prismatama Area Ciputat. Based on the results of the second hypothesis test, it was obtained that the value of t count > t table or 4,709 > 2.00030 was strengthened by the Sig value. < 0.05 or 0.000 < 0.05 H0 is rejected and H2 is accepted. So it can be concluded that partially the Compensation Variabel has a significant influence on Employee Performance at PT Indomarco Prismatama Area Ciputat. Based on the results of the third hypothesis test, it was obtained that the calculated F value > F table or 11,225 > 3.16 was reinforced by the ρ value < Sig. 0.05 or 0.000 <0.05 H0 is rejected and H3 is accepted. So it can be concluded that simultaneously the Variabels Work Environment and Compensation have a significant influence on Employee Performance at PT Indomarco Prismatama Area Ciputat